Film music : the synthesis of two art forms - a case study of themes and characters in Alfred Hitchcock's and Bernard Herrmann's Vertigo - Theunissen, Justin Robin (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMus)--Stellenbosch University, 2014.